LEARNING PROFETIC VALUES BASED ON CONTEXTUAL TEACHING AND LEARNING APPROACH IN FORMING RELIGIOUS CHARACTERS OF STUDENTS (Multi Site Study at MI Plus Sabilul Muhtadin and MI Hidayatul Mubtadi'in Wates Sumbergempol) - Hasanudin, Muhammad; Mu’awanah, Elfi; Nafis, Muhammad Muntahibun; Setyowati, Eni (PD PGMI se Indonesia, 2021)
Character education is based on the concepts taught by the Prophet in forming the morals of students for it is important to be applied in educational institutions. The objective of this study is to determine the prophetic values that are carried out in forming the religious character of students, the process of internalizing these values, and their impact by using the Contextual Teaching and Learning approach. This research uses qualitative research, with a multi-site study design. The data was collected by means of in-depth interviews, observation and documentation. The results of this study indicate that: (1) Learning of prophetic values in improving the religious character of students is by instilling prophetic values, namely fatanah, amanah, sidiq, tabligh. (2) The process of internalizing the prophetic value using the Contextual Teaching and Learning approach in improving the religious character of students, is by several stages from the planning stage, providing understanding to students, the pilot stage, the planting stage, and the habituation stage. (3) The impact of learning prophetic values using the Contextual Teaching and Learning approach in improving the religious character of students has an impact on the abilities, knowledge, and behavior of students.